Trends in Family Planning Uptake in Tanzania: An Analysis of National Survey Data 2021-2022 - Ayoub, Harun Yussuf; Prasetyo, Sabarinah (Jurnal Biostatistik, Kependudukan, dan Informatika Kesehatan, 2024)
The purpose of this study is to uncover the socioeconomic and demographic factors that influence the usage of contraceptives by analysing trends and patterns in Tanzania's family planning uptake using data from national surveys. The results show that while Tanzania has made progress in increasing contraceptive prevalence from 27% in 2010 to 39% in 2021-22, disparities persist across socioeconomic and demographic lines. Women in urban areas, from higher wealth quintiles, and with higher educational attainment have significantly higher contraceptive prevalence rates compared to their counterparts. The study also reveals that the majority of women are aware of family planning methods, and more than 75% of users get their methods from public sources. However, barriers such as sociocultural norms, spousal communication, and limited knowledge continue to hinder progress, particularly in rural areas. The study's findings offer evidence-based insights to guide the development and implementation of more successful family planning policies and programs in Tanzania, with the aim of resolving ongoing disparities in access and use of family planning services.